(untitled) (Al-Qamar, 2024)
The study was descriptive and secondary sources were consulted for the purpose. Baloch is an ancient nation who have been living in middle - East India, Balochistan and Iran since the attacks by Aryans, by different names and forms they lived in tribes, almost always attacked by foreigners and ruined because of no united power. These circumstances made alliance of Baloch tribes and they gained the advantage of driving all invaders back, no foreign ruler ever reigned in Balochistan. They fought bravely against, Cyrus of Persia, Alexander of Macedonia, Genghis Khan of Mongolia, they never allowed them to stay in Balochistan for long. The objectives behind this study are to search nation of Baloch in the historical books and find out the similarity of its ancient areas.